2012
DOI: 10.4236/abb.2012.38144
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of <i>Burkholderia cepacia</i> strain from Northeast India: A potential bio-control agent

Abstract: This paper reports the characterization of naturally occurring rhizobacteria from NE India for the control of wilt and damping-off diseases in French beans. French bean (<i>Phaseolus vulgaris</i> L.) is one of the most important food legumes for direct human consumption which was originated from South and Central America. In NE India wilt and damping-off in beans are serious diseases which are mainly caused by <i>Fusarium spp</i> and <i>Rhizoctonia solani</i>. Out of 625 bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Therefore their antagonistic activity would be related to the production of the inhibitory substances such as HCN, ammonia and chitinase. Similar observation was also obtained in various study where it have reported that production of fungal cell wall degrading enzymes (glucanase, chitinase, protease) and secondary metabolites (Siderophore and HCN) are common mechanisms associated with bacterial antifungal activities [38,39].…”
Section: Antagonistic Activity Against Phytopathogensupporting
confidence: 87%
“…Therefore their antagonistic activity would be related to the production of the inhibitory substances such as HCN, ammonia and chitinase. Similar observation was also obtained in various study where it have reported that production of fungal cell wall degrading enzymes (glucanase, chitinase, protease) and secondary metabolites (Siderophore and HCN) are common mechanisms associated with bacterial antifungal activities [38,39].…”
Section: Antagonistic Activity Against Phytopathogensupporting
confidence: 87%
“…All strains have the ability to synthesize IAA production in broth culture in the presence of tryptophan. Burkholderia cepacia IBSD-LKBI produced significant level of IAA at the rate of 58.4 lg/ml in culture filtrate (Devi et al 2012). The conversion of tryptophan into IAA is the most important mechanism of soil microbes (Mohite 2013).…”
Section: Plant Growth-promoting Activities Of Isolated Strainsmentioning
confidence: 99%
“…The ability of Psolubilizing bacteria Burkholderia or Pseudomonas cepacea to control plant diseases was also reported in other experiments. They were able to suppress Phytophthora disease in chili [16], damping off disease and Fusarium diseases in French bean [15].…”
Section: The Abilities Of Endophytic and Biofertilizing Bacteria To Smentioning
confidence: 99%
“…Azotobacter chroococcum is Nitrogen fixing bacteria that can produce exopolysaccharide [11] and has been reported to increase the growth of lettuce [12]. Some PGPR that has potential as biofertilizer can also showed suppressive effects on plant diseases [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%